Effectiveness of internal audit on organizational performance of NGOs: case study of Hivos Zimbabwe - Mahachi, Gamuchirai L. (Midlands State University, 2018)
The main objective of the study was to determine the impact of internal audit effectiveness on organizational performance of NGOs using a case study of local NGO in Zimbabwe: Case study of HIVOS .The major issue that gave rise and prompted the researcher to study across this area was increased level in project performance inefficiency and funding inefficiency which was the major reason for the organization’s stagnant growth as these two forms the major basis of the operations of non-governmental organizations. The research questions were answered using a qualitative research paradigm which incorporates a descriptive research design .Data was collected using questionnaires and interviews. A target population of 30 was used from which a sample size of 27 participants was selected using stratified random sampling. Key findings of study shows that internal audit effectiveness significantly promotes organizational performance of NGOs. 55% questionnaire response rate agreed that internal audit effectiveness promotes organizational performance and 100% interviews response rate agreeing as well .The findings confirmed that management support, organizational independence, staff competency and sound management controls enhances internal audit effectiveness. Internal audit‘s value addition in ensuring the organization‘s performance at HIVOS was not being done to the fullest thus this research provides valuable information to the organization on ways to promote internal audit effectiveness so that they organization triumphs .Also it provides valuable information to other NGOs on ways to ensure internal audit effectiveness is used to ensure the long survival of their organizations. The study recommended that HIVOS internal audit function should try to use bench marking as a tool to see how other internal audit function in their sector (NGOs) are operating and they adopt those good practices to improve their own performance.